Corporate Social responsibility, Brand Value, and Corporate Financial Performance: An empirical study from Vietnam commercial banking system - Nguyen, Hong Thu; Le, Kieu Oanh Dao; Nhan, Do Thi Thanh (CENTRAL ASIA AND THE CAUCASUS, 2021)
The study uses data from balance sheets to analyze data of 27 commercial banks from 2009 to 2020 period to find out the role of brand value (BRV) in the relationship between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP). The paper indicated from the Random Effect Model (REM) regression results and reinforcement tests that BRV is a mediator in the relationship between CSR and CFP. The empirical results also show that CSR implication helps improve BRV while there is no impact on improving CFP in state-owned commercial banks. Additionally, bank scale has a positive effect, while debt leverage negatively affects commercial banks' business performance. These findings explain the transmission mechanism between CSR and CFP. Management policies suggested enhancing the proactive implementation of CSR in pursuit of business goals in Vietnamese commercial banks.